The Relationship Between Nutritional Status, Physical Activity and Menstrual Duration with the Incidence of Anemia in Adolescent Girls at SMA Negeri 1 Boliyohuto - Nikmawati Palilati; Sunarto Kadir; Ayu Rofia Nurfadillah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Anemia occurs due to various causes, such as iron deficiency, folic acid deficiency, vitamin B12 and protein. Anemia is directly caused by insufficient production/quality of red blood cells and blood loss either acutely or chronically. The formulation of the problem is whether there is a relationship between nutritional status, physical activity and the length of menstruation with the incidence of anemia in adolescent girls at SMA Negeri 1 Boliyohuto. This study aims to analyze the relationship between nutritional status, physical activity and menstrual duration with the incidence of anemia in adolescent girls at SMA Negeri 1 Boliyohuto. The type of research is observational analysis with a research design using Cross Sectional. The population is active students in grade XI at SMA Negeri 1 Boliyohuto with a purposive sampling technique totaling 124 students. Data analysis uses Spearman Correlation. The results of the analysis of nutritional status in adolescent girls were the most common nutritional status, which was 63 students (50.8%). The most physical activity in adolescent girls was moderate physical activity as many as 82 students (66.1%). The duration of menstruation in adolescent girls was 70 students (56.5%). The results of Spearman's Correlation analysis for nutritional status were obtained with a p-value of 0.000 (p value < 0.005) with a value of r = 0.437, a physical activity p-value of 0.010 (p value < 0.005) with a value of r = -0.230 and a duration of menstruation with a p-value of 0.020 (p value < 0.005) with a value of r = 0.209. The conclusion was that there was a relationship between nutritional status, physical activity, and the duration of menstruation with the incidence of anemia in adolescent girls at SMA Negeri 1 Boliyohuto. It is hoped that this research can increase the knowledge of adolescent girls about the relationship between nutritional status, physical activity and menstrual duration and have a positive impact.